Starlike vs. classic macromolecular prodrugs: two different antibody-targeted HPMA copolymers of doxorubicin studied in vitro and in vivo as potential anticancer drugs - Jelínková, Markéta; Strohalm, Jirí; Etrych, Tomás; Ulbrich, Karel; Ríhová, Blanka (Pharmaceutical research, 2003)
PURPOSE: Two different monoclonal antibody-targeted HPMA copolymer-doxorubicin conjugates, classic and starlike, were synthesized to be used for site-specific cancer therapy. The anti-mouse Thy-1.2 (IgG3) and two anti-human CD71/A (IgG1) and CD71/B (IgG2a) monoclonal antibodies were used as targeting structures. METHODS: Their binding and cytotoxic activity in vitro, body distribution, and anticancer activity in vivo were evaluated. RESULTS: The results of flow cytometric analysis showed comparable binding of classic and starlike conjugates to the target cells. The in vitro cytotoxic effect was 10-fold higher if cancer cells were exposed to the starlike conjugate compared to the classic one. Biodistribution studies showed that the starlike conjugate remained in a relatively high concentration in blood, whereas the classic conjugate was found in a 6.5-times lower amount. In contrast to the low antitumor activity of free doxorubicin and nontargeted HPMA copolymer-doxorubicin conjugate, both anti-Thy-1.2 targeted conjugates (classic and starlike) cured all mice bearing T-cell lymphoma EL4. On the other hand, starlike conjugates containing anti-CD71/A or anti-CD71/B monoclonals as targeting structures were more effective against human colorectal cancer SW 620 than the classic one. CONCLUSIONS: We have shown that the starlike conjugates are more effective systems for targeted drug delivery and cancer treatment than classic conjugates.
Keywords: doxorubicin; buněčné dělení; lidé; Mice, Inbred BALB C; transplantace nádorů; lymfom T-buněčný; methakryláty; prekurzory léčiv; Cell Line, Tumor; Prodrugs; Antibiotics, Antineoplastic; In Vitro Techniques; Doxorubicin; Neoplasm Transplantation; molekulární struktura; tkáňová distribuce; techniky in vitro; myši; Humans; Antibodies, Monoclonal; Mice; protinádorová antibiotika; monoklonální protilátky; Molecular Structure; Methacrylates; myši inbrední BALB C; zvířata; kolorektální nádory; Mice, Inbred C57BL; Tissue Distribution; Colorectal Neoplasms; Animals; nádorové buněčné linie; Cell Division; Lymphoma, T-Cell; myši inbrední C57BL